Dynamic urinary proteomic analysis in a Walker 256 intracerebral tumor model. (15th May 2019) - Zhang, Linpei; Li, Yuqiu; Meng, Wenshu; Ni, Yanying; Gao, Youhe
Abstract: Background: Patients with primary and metastatic brain cancer have an extremely poor prognosis, mostly due to the late diagnosis of disease. Urine, which lacks homeostatic mechanisms, is an ideal biomarker source that accumulates early and highly sensitive changes to provide information about the early stage of disease. Methods: A rat model mimicking the local tumor growth process in the brain was established with intracerebral Walker 256 (W256) cell injection. Urine samples were collected on days 3, 5, and 8 after injection, and then analyzed by liquid chromatography coupled with tandem mass spectrometry. Results: In the intracerebral W256 model, no obvious clinical manifestations or abnormal magnetic resonance imaging (MRI) signals were found on days 3 or 5; at these time points, 9 proteins were changed significantly in the urine of all eight tumor rats. On day 8, when tumors were detected by MRI, 25 differential proteins were identified, including 10 that have been reported to be closely related to brain metastasis or primary tumors. The differential urinary proteome was compared with those from the subcutaneous W256 model and the intracerebral C6 model. Few differential proteins overlapped, and specific differential protein patterns were observed among the three models. Conclusions: These findings demonstrate that early changes in the urine proteome can be detected in the intracerebral W256 model. The urinary proteome can reflect the difference when tumor cells with different growth characteristics are inoculated into the brain and when identical tumor cells are inoculated into different areas, specifically, the subcutis and the brain. Abstract : Changes caused by intracerebral Walker 256 cells injection can be reflected early in urinary proteins. The urinary proteome can reflect the difference when tumor cells with different growth characteristics are inoculated into the brain and when identical tumor cells are inoculated into different areas, specifically, the subcutis and the brain.